2012
DOI: 10.1038/oby.2012.25
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and Obesity in Military Personnel: Sociodemographic Predictors

Abstract: In the United States, nationally representative civilian studies have shown that BMI is associated with select sociodemographic characteristics. Active‐duty military personnel are not included in these surveys and the persistence of these associations in military personnel is unknown. Data from the worldwide, representative 2002 and 2005 Department of Defense (DoD) Surveys of Health‐Related Behaviors Among Active Duty Military Personnel were used to assess the prevalence of overweight and obesity and, the asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
73
1
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(93 citation statements)
references
References 16 publications
8
73
1
7
Order By: Relevance
“…Figure 2 shows a cluster of studies with above-average obesity prevalence data among firefighters (7,35,83,112), although lower estimates were also reported (33,60). A cluster of studies for the military showed below-average estimates (49,65,107). Firefighters and law-enforcement personnel have previously displayed higher levels of risk related to cardiovascular disease, including overweight and obesity (100).…”
Section: Obesitymentioning
confidence: 97%
“…Figure 2 shows a cluster of studies with above-average obesity prevalence data among firefighters (7,35,83,112), although lower estimates were also reported (33,60). A cluster of studies for the military showed below-average estimates (49,65,107). Firefighters and law-enforcement personnel have previously displayed higher levels of risk related to cardiovascular disease, including overweight and obesity (100).…”
Section: Obesitymentioning
confidence: 97%
“…Obesity prevalence was high compared to that of the general US population or military personnel, among whom obesity prevalence is estimated at 38% and 13%, respectively. 1,13 However, comparisons must be interpreted with the understanding that VHA data reflect a treatment-seeking population, who may be older and sicker than the general population. [14][15][16][17][18] Furthermore, while findings reflect the universe of veterans using VHA, they may not apply to veterans outside the VHA, who tend to be in better health.…”
Section: Discussionmentioning
confidence: 99%
“…como en México, China, Suecia y Australia se mantiene una preocupación prioritaria por los costes económicos del sistema sanitario. Coste que incluyen tanto la atención médica relacionada con la obesidad como las bajas por enfermedad y la productividad laboral, pues están creando potenciales efectos a largo plazo sobre la competitividad económi-ca y poniendo en peligro la propia seguridad nacional [44][45][46] . Vistas las consecuencias se está planteando valorar la obesidad a la hora de realizar los contratos laborales y el mantenimiento de los mismos para el personal de las FF.AA.…”
Section: Intervención Sobre Los Factores De Riesgo Vascularunclassified